Knowledge Integration in the Scientific Heritage of Central Asian Scolars (International Journal of Psychosocial Rehabilitation, 2020)
The author of the article reviews the idea of the development of knowledge integration in the works of great medieval Oriental scholars Al-Farabi, Al-Khwarizmi, and others. Concurrence of this process is presented through works of scholars in which mathematics is integrated with music, art, and architecture.